Relationship between Exposureto Class Size Reductionand Student Achievementin California - Stecher, Brian M.; McCaffrey, Daniel F.; Bugliari, Delia (Education Policy Analysis Archives, 2003)
The CSR Research Consortium has been evaluating the implementation of the Class Size Reduction initiative in California since 1998. Initial reports documented the implementation of the program and its impact on the teacher workforce, the teaching of mathematics and Language Arts, parental involvement and student achievement. This study examines the relationship between student achievement and the number of years students have been exposed to CSR in grades K-3. The analysis was conducted at the grade level within schools using student achievement data collected in 1998-2001. Archival data collected by the state were used to establish CSR participation by grade for each school in the state. Most students had one of two patterns of exposure to CSR, which differed by only one year during grade K-3. The analysis found no strong association between achievement and exposure to CSR for these groups, after controlling for pre-existing differences in the groups.